Indonesian EFL students' strategies in dealing with speaking anxiety in public speaking course - Ayuna Netta; Ika Kana Trisnawati; Cut Mawar Helmanda (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2020)
Public Speaking is one of the courses learned by the students at universities. In this pilot study, the purpose was to investigate the students’ strategies in coping with anxiety in English Public Speaking course. Participants of the study were two junior students of English Education Department of Universitas Muhammadiyah Aceh, Banda Aceh in Aceh Province, Indonesia. The study purposively selected them based on their gender and class engagement in the Public Speaking course in 2019/2020 academic year. The study used the qualitative method, with interview to collect the data. Findings showed that the students applied several strategies to deal with their speech anxiety, including having adequate preparation and practice and using hand and body movements when delivering a speech. This study recommends that teachers promote such strategies to other EFL students so that they can overcome their fear of public speaking.